2010
DOI: 10.3324/haematol.2009.013714
|View full text |Cite
|
Sign up to set email alerts
|

Splenic diffuse red pulp small B-cell lymphoma: revision of a series of cases reveals characteristic clinico-pathological features

Abstract: BackgroundSplenic diffuse red pulp small B-cell lymphoma is an uncommon B-cell lymphoma, now recognized as a provisional entity in the 2008 update of the WHO Classification. Additional work is required to review this entity and establish its diagnostic features. Design and MethodsWe have retrospectively analyzed the disease features in a highly selected series of 17 patients diagnosed as splenic diffuse red pulp small B-cell lymphoma. ResultsThe median age was 65.5 years (range 40-79 years) and there was a pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
2
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(103 citation statements)
references
References 14 publications
3
88
2
10
Order By: Relevance
“…There may be blood lakes. 68,69 In the bone marrow, there is usually striking intrasinusoidal infiltration usually with an interstitial component ( Figure 5). The peripheral blood shows small cells that have scanty cytoplasm and nuclei with clumped chromatin.…”
Section: Splenic Diffuse Red Pulp Small B-cell Lymphomamentioning
confidence: 99%
“…There may be blood lakes. 68,69 In the bone marrow, there is usually striking intrasinusoidal infiltration usually with an interstitial component ( Figure 5). The peripheral blood shows small cells that have scanty cytoplasm and nuclei with clumped chromatin.…”
Section: Splenic Diffuse Red Pulp Small B-cell Lymphomamentioning
confidence: 99%
“…Однако критерии диагностики остаются малоизученным вопросом. В литературе присутствуют крайне немногочисленные сведения, посвященные диффузной В-клеточной лимфоме красной пульпы селезенки с описанием диагностических критериев при исследовании операционного материала (спленэктомия) [1]. Нередко публикации по данному вопросу содержат описания отдельных наблюдений с диа-гностикой по материалу трепанобиоптатов костного мозга.…”
Section: Introductionunclassified
“…In order to make the search as wide as possible, no limits were applied regarding the date of publication, the language or the research design The most common finding in the bone marrow biopsies was predominance of intrasinusoidal lymphoid infiltration, some- Kanellis et al 2 found p53 inactivation in all cases of splenic diffuse red-pulp small B-cell lymphoma, comprising either p53 mutation (2/4 cases) or anomalous p53 staining. Mollejo et al 4 reported that TP53 abnormality was present in 2 out of 13 cases (15.3%): one of these patients showed disease progression and ultimately died of the disease.…”
Section: Casementioning
confidence: 99%
“…1 This new WHO update recognized two categories of primary splenic lymphomas; splenic marginal-zone lymphoma (SMZL) and the provisional group of splenic B-cell lymphoma/leukemia unclassifiable (SLLU), that includes splenic diffuse red-pulp small B-cell lymphoma and hairy-cell leukemia variant (HCL-v). 1 The median age at which patients are diagnosed with splenic diffuse red-pulp small B-cell lymphoma is 72 years (range: 69-74 years), 2 and the disease is seen predominantly among males, with a male/female ratio of 2.4:1.…”
Section: Introductionmentioning
confidence: 99%